Pitavastatin ameliorated the progression of steatohepatitis in ovariectomized mice fed a high fat and high cholesterol diet. Issue 4 (13th September 2012) - Kamada, Yoshihiro; Kiso, Shinichi; Yoshida, Yuichi; Chatani, Norihiro; Kizu, Takashi; Hamano, Mina; Egawa, Mayumi; Takemura, Takayo; Ezaki, Hisao; Furuta, Kunimaro; Hayashi, Norio; Takehara, Tetsuo
<x xml:space="preserve">Abstract</x> Aim Many studies indicate an accelerated progression of non‐alcoholic steatohepatitis (NASH) in postmenopausal women. Very recently, we reported that estrogen deficiency enhanced the progression of steatohepatitis in mice fed a high fat and high cholesterol (HFHC) diet. Hypercholesterolemia is often observed in postmenopausal women, and recent studies indicate it to be an important risk factor for the progression of NASH. Statins can slow NASH progression in the estrogen‐deficient state but the precise mechanisms of their effects are still unclear. Methods We investigated the effects of pitavastatin on steatohepatitis progression using ovariectomized (OVX) mice fed a HFHC diet or HFHC + pitava diet (containing 5 p.p.m. pitavastatin) for 6 weeks. Results Serum alanine aminotransferase and cholesterol levels significantly decreased in mice fed the HFHC + pitava diet compared with mice fed the HFHC diet. Real‐time reverse transcription polymerase chain reaction representing hepatic inflammatory gene expressions significantly decreased in mice fed the HFHC + pitava diet compared with the HFHC‐fed mice. Pitavastatin treatment also decreased both hepatic macrophage infiltration and hepatocyte chemokine (C‐C motif) ligand 2 expression and improved the liver fibrosis condition when compared with the mice fed the HFHC diet. In addition, the enhanced spleen monocyte chemokine (C‐C motif) receptor 2 expression in ovariectomized mice fed the HFHC diet was also decreased by pitavastatin administration. Conclusion Our study demonstrated that the exacerbated steatohepatitis progression in OVX mice fed a HFHC diet could be attenuated by pitavastatin treatment at least through inhibition of hepatic macrophage infiltration. We concluded that statins should be useful for treating NASH in postmenopausal women.